A Main Peak Extraction Method for High-Order BOC Signals. (30th May 2017) - Liu, Fang; Feng, Yongxin
Abstract : Binary Offset Carrier (BOC) modulation signals have been applied in Global Navigation Satellite Systems (GNSS) because they offer a higher positioning accuracy and higher multipath rejection. However, there is a drawback in that the autocorrelation functions have multiple side peaks, meaning that this technique also leads to the large main peak estimation error problem and a low correlation decision efficiency problem. In this paper, we propose a new Main Peak Extraction (MPE) method for high-order BOC signals to solve these problems. In the new method, the synthesis cross-correlation function is established, and the geometry graph is formatted to calculate the estimation main peak. We eliminate all side peaks and improve the main peak phase estimation precision under the condition that the sub-carrier phase is offset. The results of the simulation demonstrate that the new method can achieve better main peak decision efficiency, side peak cancellation ability and phase estimation performance than traditional methods.